Analisis Kecerdasan Verbal Linguistik Peserta Didik Dalam Pembelajaran Kooperatif - Rahman, Indra Nur Rahman (Perspektif Ilmu Pendidikan, 2022)
Abstract: Education is a tool that everyone needs to acquire knowledge. Through education, students gain a lot of knowledge through the learning process. The learning process takes place as a form of processing information that students get from the surrounding environment. The process of obtaining and processing information requires good communication skills. This research method is descriptive qualitative. The purpose of this paper is to provide an overview of students' linguistic communication skills. The results of this study indicate that linguistic intelligence can be improved through several strategies implemented by educators. Keywords: Education, Communication Skills, Verbal Linguistics